Speed-dependent Automatic Zooming for Browsing Large Documents - Igarashi, Takeo; Hinckley, Ken (UIST '00 Proceedings of the 13th annual ACM symposium on User interface software and technology, 2000)
We propose a navigation technique for browsing large documents that integrates rate-based scrolling with automatic zooming. The view automatically zooms out when the user scrolls rapidly so that the perceptual scrolling speed in screen space remains constant. As a result, the user can efficiently and smoothly navigate through a large document without becoming disoriented by extremely fast visual flow. By incorporating semantic zooming techniques, the user can smoothly access a global overview of the document during rate-based scrolling. We implemented several prototype systems, including a web browser, map viewer, image browser, and dictionary viewer. An informal usability study suggests that for a document browsing task, most subjects prefer automatic zooming and the technique exhibits approximately equal performance time to scroll bars, suggesting that automatic zooming is a helpful alternative to traditional scrolling when the zoomed out view provides appropriate visual cues.